Enhancement of medical student performance through narrative reflective practice: a pilot project - Thomson, Alan; Harley, Dwight; Cave, Marie; Clandinin, Jean (Canadian Medical Education Journal, 2013)
Background: Narrative Reflective Practice (NRP) is a process that helps medical students become better listeners and physicians. We hypothesized that NRP would enhance students’ performance on multiple choice question exams (MCQs), on objective structured clinical examinations (OSCEs), and on subjective clinical evaluations (SCEs). Methods: The MCQs, OSCEs and SCEs test scores from 139 third year University of Alberta medical students from the same class doing their Internal Medicine rotation were collected over a 12 month period. All preceptors followed the same one-hour clinical teaching format, except for the single preceptor who incorporated 2 weeks of NRP in the usual clinical teaching of 16 students. The testing was done at the end of each 8-week rotation, and all students within each cohort received the same MCQs, OSCE and SCEs Results: Independent t-tests were used to assess group differences in the mean MCQ, OSCE and SCE scores. The group receiving NRP training scored 4.7 % higher on the MCQ component than those who did not. The mean differences for OSCE and SCE scores were non-significant. Conclusions: Two weeks NRP exposure produced an absolute increase in students’ MCQ score. Longer periods of NRP exposure may also increase the OSCE and SCE scores. This promising pilot project needs to be confirmed using several trained preceptors and trainees at different levels of their clinical experience.